Analysis of The Effect of Post Weld Heat Treatment (PWHT) on The Hardness and Corrosion Rate of SMAW Welded Joints on AISI 304 Plates - Diantoro, Helga; Jumiadi, Jumiadi; Widyastuti, Ike (TRANSMISI, 2024)
Post-welding heat treatment (PWHT) is a heat treatment of steel that has undergone welding. The purpose of doing PWHT is to improve the properties of the material itself. Such as uniforming the microstructure, reducing residual stresses, and improving corrosion resistance. In this study the authors conducted a shielded arc welding (SMAW) welding experiment on an AISI 304 steel pelate which had a thickness of 8 mm, a width of 150 mm, and a length of 200 mm. AISI 304 is a type of austenitic stainless steel. The type of seam used is the v seam with an angle of 60˚ and a root face of 2 mm. As for the welding process, it was carried out in the 1G position, using an E308S-15 electrode with a diameter of 2 mm, and a current of 60 A. From the welding carried out on the AISI 304 pelate, then cuts were made to divide the steel into 10 specimens, with a width of 10 mm, a thickness of 8 mm, and 60 mm long. PWHT was carried out with temperature variations of 1100˚C, 900˚C and 700˚C for 15 minutes, and cooled using water as the medium. Conclusions that can be drawn from this research, among others; (1) From the PWHT process carried out at temperatures of 1100˚C, 900˚C and 700˚C. Temperature of 1100˚C can reduce carbide deposition in the weld metal, HAZ and base metal areas, (2) The highest level of hardness occurs in the weld metal area without PWHT of 111.7 HRB, while the lowest hardness level occurs in the HAZ area with PWHT of 1100˚C as big as 95.6 HRB. (3) The highest corrosion rate occurred at PWHT 700˚C of 0.429 mm/y, while the lowest corrosion rate occurred at PWHT 1100˚C of 0.073 mm/y.